Verkehrschaos oder Green Cities? Städte der Zukunft. - Leschus, Leon; Stiller, Silvia; Vöpel, Henning (Deutscher Verkehrs-Verl., 2010)
Die Motorisierung der Weltbevölkerung und das Verkehrsaufkommen werden zukünftig drastisch ansteigen, insbesondere in Städten. Die zentralen Triebkräfte hierfür sind das immense Wachstum der Weltbevölkerung, die rasant steigenden Einkommen in zahlreichen Regionen der Welt sowie die ungebremst voranschreitende Urbanisierung. Lärm, Luftverschmutzung und Staus werden zunehmend das Bild wachsender Metropolen prägen und verlangen nach Lösungsansätzen zur zukunftsweisenden Gestaltung von Mobilität - wie können diese aussehen?

The motorization of the world's population and the volume of traffic are deemed to grow in future without any form of restraint, The main driving forces behind this are both the enormous growth in population and the rapidly rising levels of income in various regions of the world. Leading up to 2030, passenger car density (the number of cars per inhabitant) is likely to increase threefold in India, fourfold in Indonesia, and tenfold in China. At the same time, urbanization is going to continue and will affect especially those countries. It is for this reason that this ongoing growth in motorization will place new demands on areas of high population density and mega cities. Related problems will increase in line with traffic development, while noise, pollution and traffic jams will emerge as the main characteristics of expanding metropolitan areas. The report highlights the development of both the motorization of the world's population and ongoing urbanization in the course of the forthcoming decades, and their anticipated impact on the development of urban areas.
Cities of the future - between transport chaos and a green environment.
Keywords: Verkehr; Verkehrspolitik; Personenverkehr; Mobilität; Stadtverkehr; Individualverkehr; Kraftfahrzeug; Autoverkehr; Verkehrsnachfrage; Verkehrsaufkommen; Verkehrsprognose; Verkehrsstatistik; Bevölkerungsstatistik; Nachhaltigkeit; Stadtentwicklungspolitik; Mega-City